Tinjauan Hak Pekerja Kontrak Atas Pemutusan Hubungan Kerja Sepihak - Daniel Marshal Sajou; Gunardi Lie (Syntax Corporation, 2023)
Termination of Employment occurs based on the previous employment relationship created between the worker/laborer and the employer which is marked by an agreement in the employment agreement. Contract workers are bound by a Specific Time Work Agreement (PKWT). Layoff is something that is highly avoided, especially for workers/laborers because since the layoff occurs, at that time the worker/laborer also loses their livelihood and loses the ability to meet their daily needs, so workers' rights must be protected. This research aims to understand the rights of contract workers who experience unilateral termination of employment (PHK) during the contract. The method in this research is normative legal research by searching and connecting legal facts with the basis of regulations to create conclusions to answer the problems that arise. The results of the research found that 1) The regulation of unilateral termination by the employer is contained in Article 62 of the Labor Law; 2) In the case of PT Vietmindo Energitama there was an imbalance because the judge of the Industrial Relations Court rejected the plaintiff's claim which the employer did not fulfill. This, it creates losses and does not create certainty for workers/laborers because it is clearly and rigidly regulated that the party terminating the employment relationship is obliged to pay compensation until the contract period ends.